ANALYSIS OF MATHEMATIC CREATIVE THINKING ABILITY OF SMP NEGERI 1 SUKARAJA STUDENTS VIEWED FROM SELF-EFFICACY - Nurrahmi, Finna; Lukman, Hamidah Suryani; Mulyanti, Yanti (De Fermat : Jurnal Pendidikan Matematika, 2024)
The purpose of this study was to knowing the mathematical creative thinking abilities of class VII students at SMP Negeri 1 Sukaraja in terms of self-efficacy on the subject of triangles and quadrilateral. The research method used is descriptive qualitative. The instrument used was a test instrument on a rectangular and triangular material with question matter and non-test instrument in the form of a self-efficacy questionnaire. The sample in this study were 6 grade VII students at SMP Negeri 1 Sukaraja which were divided into two high and low self-efficacy groups, but had the same level of mathematical creative thinking ability. The results of this study are that there is a relationship between self-efficacy and students' creative thinking abilities on triangular and quadrilateral material. Judging from the achievement of the subject in solving problems shows that for students with low self-efficacy only meet two aspects of the four existing aspects, namely fluency and elaboration. On the other hand, students with high self-efficacy tend to fulfill all four aspects, namely fluency, flexibility, elaboration and originality.